Про одну нерівність для третього модуля неперервності - Нестеренко, О. Н. (My University, 2013)
The work is devoted to the study of the properties of modulus of continuity of higher-order, which are an important characterization of the smoothness of nondifferentiable functions. We consider that the uniform modulus of continuity of higher orders for real-valued functions of a real variable is uniformly continuous on the whole real axis. У статті досліджено властивості модулів неперервності старших порядків, які є важливою характеристикою гладкості недиференційовних функцій . Розглянуто рівномірні модулі неперервності старших порядків для дійсно значних функцій дійсної змінної, рівномірно неперервних на всій дійсній осі .
Keywords: inequality; uniformly continuous; function; finite difference; the modulus of continuity of the third order; модуль неперервності третього порядку; нерівність; рівномірно неперервна функція; скінченна різниця